Inside-Out, or Outside-in?: Woman in a glasshouse at the residence of Louis P Christeson at 213 Willis Street, Wellington (ca 1890s) - Wood, Peter (Architectural History Aotearoa, 2023)
This research draws its subject, and its sub-title, from a photograph taken by Louis P Christeson, in which a female figure is depicted tending to the potted inhabitants of a small conservatory. Using this image as a reference point, this paper discusses the conservatory as a transgressive space that is neither properly inside, nor properly outside, the houses and gardens they are associated to. Specifically, a conservatory enables the creation of fertile artificial climates to support flora specimens that would otherwise not find a horticulturally receptive environment. As an architectural technology, its history well precedes the 1890s, but it is in this decade that the conservatory's role expanded from its agricultural origins to affect representations of social and cultural transaction. Or, in simple terms, though the 1890s a conservatory was increasingly just as likely to feature people as it was plants. With conservatories, simple divisions of interiority and exteriority, and normative expectations of public and private distinctions, become far more mobile in their spatial classifications. In this regard, the 1890s are a particularly important decade for the conservatory as it shifted from being a tool of horticultural propagation to become a new expression of social and cultural production that conflated the distinctions between interior and exterior, and linking this to individual economic progress. Bringing this argument back to my reference photograph, I suggest that for Louis P Christeson, the conservatory was profoundly important symbol of middle-class arrival as exemplified by home ownership and leisure interests, both of which utilised the conservatory as a "third-space." It cannot be claimed that the conservatory led societal evolution, but it does provide a useful architectural touchstone for registering how the relationship between interior and landscape changed as a consequence.